2005
DOI: 10.1073/pnas.0404977102
|View full text |Cite
|
Sign up to set email alerts
|

Soil animals alter plant litter diversity effects on decomposition

Abstract: Most of the terrestrial net primary production enters the decomposer system as dead organic matter, and the subsequent recycling of C and nutrients are key processes for the functioning of ecosystems and the delivery of ecosystem goods and services. Although climatic and substrate quality controls are reasonably well understood, the functional role of biodiversity for biogeochemical cycles remains elusive. Here we ask how altering litter species diversity affects species-specific decomposition rates and whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
329
7
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 408 publications
(367 citation statements)
references
References 35 publications
23
329
7
8
Order By: Relevance
“…R. Soc. B 281: 20141682 mixture decomposition has rarely been considered in previous studies, but the few extra-tropical studies specifically testing for soil fauna effects found that non-additive effects on litter mixture decomposition were mostly attributed to the presence of fauna [36][37][38][39][40]. Fauna could reinforce the litter mixtures effects directly through higher litter consumption in mixtures (owing to complementary uptake of resources from a mixed diet [36] and/or as a result of diluted inhibitory compounds [41]) and/or indirectly by altering the microbial decomposer activity.…”
Section: Discussionmentioning
confidence: 99%
“…R. Soc. B 281: 20141682 mixture decomposition has rarely been considered in previous studies, but the few extra-tropical studies specifically testing for soil fauna effects found that non-additive effects on litter mixture decomposition were mostly attributed to the presence of fauna [36][37][38][39][40]. Fauna could reinforce the litter mixtures effects directly through higher litter consumption in mixtures (owing to complementary uptake of resources from a mixed diet [36] and/or as a result of diluted inhibitory compounds [41]) and/or indirectly by altering the microbial decomposer activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although this mesh size may successfully avoid the physical loss of lower-order roots, it actually impedes the access of soil fauna into litterbags. Soil fauna plays an important role in litter decomposition and determines the magnitude and direction of litter diversity effects (Hättenschwiler and Gasser 2005). Hence, the lack of involvement of soil fauna may, to some extent, affect the pattern of the mixing effect.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the presence of some secondary plant metabolites, such as polyphenols, may decrease, revert, or even compensate synergistic mechanisms that would be occurring simultaneously. This effect would decrease the decomposition rate of litter mixture, when compared to the sum of decomposition rates observed in each of the species composing the mixture, causing the antagonistic effect [51,59]. Thus, plant diversity that composes the litter mixture would not always have the expected positive effect on decomposition.…”
Section: The Process Model -Litter Decompositionmentioning
confidence: 99%
“…These organisms remove, mix, break and digest the organic matter, metabolizing litter constituents, mineralizing and making nutrients available to plants [51]. Even though all components of the edaphic biota may perform important roles on litter decomposition, the main decomposing agents are fungi and bacteria, being responsible by nutrient mineralization.…”
Section: The Process Model -Litter Decompositionmentioning
confidence: 99%
See 1 more Smart Citation